2019
DOI: 10.1213/xaa.0000000000001002
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Intravenous Lidocaine Infusion Adverse Reaction: A Case Report

Abstract: Intravenous lidocaine is increasingly being utilized as an opioid-sparing analgesic. A 55-year-old man with well-controlled human immunodeficiency virus on highly active antiretroviral therapy was prescribed a lidocaine infusion at 1 mg/kg/h for postoperative pain. On postoperative day 2, the patient experienced 4 unresponsive episodes with tachycardia, hypertension, and oxygen desaturation. Serum lidocaine level was available 2 days later (high 6.3 µg/mL, therapeutic range 2.5–3.5 µg/mL). There is significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Although the patient recovered after a few days, this case highlights the importance of using IV lidocaine judiciously, especially when a patient is on several medications, a few of which are metabolized by the CYP3A4 enzyme (39). Lidocaine levels should be monitored carefully and should remain within the therapeutic range as levels beyond 10mcg/mL, as seen in this patient, are associated with ventricular arrhythmias (40). See Table 2.…”
Section: Headachementioning
confidence: 86%
“…Although the patient recovered after a few days, this case highlights the importance of using IV lidocaine judiciously, especially when a patient is on several medications, a few of which are metabolized by the CYP3A4 enzyme (39). Lidocaine levels should be monitored carefully and should remain within the therapeutic range as levels beyond 10mcg/mL, as seen in this patient, are associated with ventricular arrhythmias (40). See Table 2.…”
Section: Headachementioning
confidence: 86%
“…Kramer et al reported that a patient with HIV who was receiving highly effective antiretroviral therapy experienced four unresponsive episodes with tachycardia, hypertension, and oxygen desaturation on the 2nd day after the operation. 37 In the proposed trial, we will strictly limit the participants to those with ASA grades I-II. At the same time, to identify and manage potential adverse events in a timely manner, all participants will be monitored closely when the study drug is administered.…”
Section: Discussionmentioning
confidence: 99%
“…There were 11 (31%) cases of obvious overdosing of the drug, 10 (91%) of which were due to lidocaine and one (9%) was due to bupivacaine. The three cases of therapeutic intravenous lidocaine infusion involved administration of a total dose of 1.5-2 mg.kg À1 with the highest reported serum lidocaine level of 16 µg.ml À1 [19,30,35]. One case of intravenous injection resulted from the miscalculation of a dose intended for treatment of laryngospasm in a paediatric patient [13].…”
Section: Ropivacaine and Bupivacaine Individually Each Accountedmentioning
confidence: 99%
“…Between December 2017 and May 2020, there were a further 36 cases of LAST reported in 34 peer‐reviewed published articles [6–39]. These data indicated 30% of patients were older than 65 y, and 6% were younger than 5 y. Sixty‐one percent of cases occurred in the hospital; 17% in outpatient surgery centres; and 14% in outpatient clinics (e.g.…”
Section: Clinical Presentationmentioning
confidence: 99%